Weverse Platform Use in CARAT SEVENTEEN Fandom Practices: Penggunaan Platform Weverse dalam Praktik Fandom CARAT SEVENTEEN - Muhammad Randi Fauzi; Ferry Adhi Dharma (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Digital media platforms function as major spaces for fandom communication, facilitating interaction, identity expression, and cultural content access. Specific Background: CARAT, the fandom of SEVENTEEN, actively uses the Weverse application as a dedicated platform for communication with idols and fellow fans. Knowledge Gap: Limited academic discussion exists on how Weverse fulfills multiple fandom needs within an integrated platform environment. Aims: This study examines the use of Weverse by CARAT SEVENTEEN fandom members through the Uses and Gratifications perspective. Results: Using a qualitative descriptive approach involving interviews and observations of five active CARAT users aged 18–25 years, the findings indicate that Weverse provides official information, entertainment, social interaction, emotional expression, and identity construction. Platform features such as exclusive feeds, live interaction, Fan Letter, streaming, and voting support communication between idols and fans and strengthen interaction among fandom members. Challenges include language barriers, fake accounts, and limited live translation, yet users still prioritize Weverse over general social media platforms. Novelty: This study presents a concise depiction of multi-dimensional gratification achieved through a specialized K-pop fandom platform. Implications: The findings contribute to communication studies by clarifying the role of specialized digital platforms in shaping fandom interaction, identity representation, and information consumption patterns. Highlights: Official Updates and Exclusive Content Position the Platform as a Primary Reference Source. Interactive Features Facilitate Emotional Expression and Mutual Support Among Community Members. Identity Expression Is Manifested Through Profiles, Symbols, and Participatory Fan Activities. Keywords: Weverse Platform, K-Pop Fandom, Carat Seventeen, Uses and Gratifications, Digital Fan Interaction